Sex and gender in society - Nielsen, Joyce McCarl (Waveland Press, 1990)
Includes bibliographical references (p. 261-275) and index.; Rev. ed. of: Sex in society. c1978; Neal A. Newfield, Ph.D., LICSW (Giver)